Inverted urothelial papilloma: A case report - Raj A. Kumar (Elsevier, 2022)
Inverted urothelial papilloma (IUP) is an unusual tumor that typically presents as a non-invasive, endophytic urothelial neoplasm. Though fairly well described in the bladder, IUP of the upper urinary tract is fairly rare, with only 68 cases documented in English language literature. Our patient presented with an IUP of the distal left ureter and was treated with a distal ureterectomy and reimplant of the ureter with a psoas hitch.